Factors influencing student engagement in online ideological and political education: a qualitative study of vocational college students in China - Chunxiu, Sun; Saleh, Abdulrazak Yahya (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
The COVID-19 pandemic accelerated the global shift to online education, exposing both opportunities and challenges in ideological and political (I&P) courses at Chinese higher vocational colleges, where student engagement remains pivotal yet underexplored. This qualitative study examines how students perceive and experience engagement in online I&P courses, framed by Activity Theory, Social Interaction, and Critical Pedagogy. Semi-structured interviews were conducted with 30 students (15 males, 15 females; freshman to junior cohorts) from Anhui Vocational and Technical College, using Tencent Meetings for 30-minute sessions. Thematic analysis identified two core themes: (1) Infrastructure—students emphasized the necessity of clear rules, stable platforms (e.g., MOOCs, ClassIn), and teacher responsiveness to foster accountability; (2) Engagement Dynamics—peer collaboration, real-world case studies, and critical discussions enhanced motivation, while poor internet connectivity, abstract content, and self-regulation struggles impeded participation. Notably, students highlighted the transformative potential of interactive tools (e.g., real-time Q&A, role-playing simulations) in bridging theory and practice. Limitations include the single-institution sample, potential response bias, and lack of longitudinal data. Nevertheless, findings offer actionable insights: educators should design modular content aligned with vocational contexts, integrate adaptive technologies to mitigate connectivity issues, and implement structured peer-review systems to sustain motivation. Institutional support for digital literacy training and hybrid learning models is also critical. Future research should expand to diverse regions, incorporate mixed methods, and track long-term outcomes to strengthen pedagogical strategies in online I&P education.